(untitled) (Italiano LinguaDue, 2021)
Il contributo presenta e commenta i risultati di una sperimentazione didattica condotta nell’anno scolastico 2017/2018 in due classi terze di una scuola primaria della provincia di Viterbo, un’area caratterizzata da un’elevata incidenza di alunni stranieri sul totale degli iscritti in tutti gli ordini scolastici. La sperimentazione, ispirata al progetto Osservare l’interlingua, si è concentrata sull’apprendimento della scrittura descrittiva e narrativa e sui problemi incontrati da alunni con differenti difficoltà di apprendimento. Il contributo dà conto di come gli alunni e soprattutto le insegnanti hanno valutato la sperimentazione. Teaching of writing to primary school’s pupils in multilingual classes. Results of an experimentation This paper presents and comments on the results of an educational experience conducted during the 2017/2018 school year in two third-grade classes at a primary school in the province of Viterbo, in an area characterized by a high incidence of foreign students enrolled in both primary and secondary school levels. Modelled after the Osservare l’interlingua Project, the experience focused on the learning of descriptive and narrative writing and the problems faced by students with different learning difficulties. The paper briefly reports the students’ and especially the teachers’ comments.